The Problem of Interpreting Cluster B Personality Disorders: at the Intersection of Psychiatry and Morality - Rogoża-Žuklys, Daniel; Bartkienė, Aistė (Problemos, 2022)
In medicine, some personality traits, involving specific patterns of thought, feeling, and behavior, are considered to be pathological. Personality types, characteristic of such pervasive and maladaptive traits, are known under the term “personality disorders.” However, some of these pathological traits, diagnostic of so-called Cluster B personality disorders, largely describe immoral behavior. Hence, the question arises as to how such immoral behavior could be framed also as a medical problem. Moreover, it is not immediately clear whether persons with these disorders could be held responsible for their immoral actions. By drawing on virtue ethics and the concept of responsibility without blame, the article demonstrates how the problem of compatibility between medicalization, cultivation of moral character, and responsibility could be resolved. Thereby, it is suggested that Cluster B personality disorders are best understood as both a moral and medical problem.
Keywords: Cluster B personality disorders; morality; medicalization; responsibility without blame; virtue ethics